2023
DOI: 10.1128/iai.00035-23
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus Drives Major Transcriptomic Changes in the Colonic Epithelium

Abstract: Group B Streptococcus (GBS) is a leading cause of infant sepsis worldwide. Colonization of the gastrointestinal tract is a critical precursor to late-onset disease in exposed newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…We found that GBS meningitis is associated with more severe clinical manifestations and worse long-term neurological outcomes in neonates. Most of the GBS isolates that caused neonatal meningitis in our cohort belong to the type III/CC17 and type Ib/CC12 strains, which is compatible with previous studies [4,6,[21][22][23][24]. WGS was used to investigate the genetic differences between the GBS isolates of neonatal meningitis and those that caused neonatal sepsis in our cohort, and we found the presence of BspC, HvgA, and PezT genes, as well as ICESag37, to be potentially associated with the occurrence of GBS meningitis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that GBS meningitis is associated with more severe clinical manifestations and worse long-term neurological outcomes in neonates. Most of the GBS isolates that caused neonatal meningitis in our cohort belong to the type III/CC17 and type Ib/CC12 strains, which is compatible with previous studies [4,6,[21][22][23][24]. WGS was used to investigate the genetic differences between the GBS isolates of neonatal meningitis and those that caused neonatal sepsis in our cohort, and we found the presence of BspC, HvgA, and PezT genes, as well as ICESag37, to be potentially associated with the occurrence of GBS meningitis.…”
Section: Discussionsupporting
confidence: 89%
“…Compared to numerous studies that have investigated the molecular epidemiology of neonatal GBS invasive diseases and colonization in pregnant women, relatively fewer studies have focused on GBS meningitis [4,21,22]. We found that GBS meningitis is associated with more severe clinical manifestations and worse long-term neurological outcomes in neonates.…”
Section: Discussionmentioning
confidence: 61%
“…After birth, GBS is capable of colonizing the infant GI tract and can subsequently disrupt the intestinal barrier and spread systemically to the brain, resulting in meningitis and LOD. Previous studies have used murine neonatal models of GBS LOD that use either oral gavage of postnatal day 5 (P5) and P10 pups or intraperitoneal injection of P2 and P5 pups ( 16 , 19 21 , 33 ). We sought to modify the P2 neonatal meningitis infection model to incorporate direct GI colonization of P2 pups to mimic LOD at this age ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also determined that GBS glycolipids are important for bloodstream survival in an established hematogenous murine model of meningitis. To further investigate GBS LOD, we adapted a neonatal meningitis model ( 16 , 19 , 20 , 33 ) by directly seeding the gut of P2 mice with GBS and monitoring systemic spread. In neonatal mice, we observed significant attenuation of GBS∆ iagB with decreased bloodstream survival compared to WT GBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation